Irradiation uniformity at the Laser MegaJoule facility in the context of the shock ignition scheme. (1st April 2014) - Temporal, Mauro; Canaud, Benoit; Garbett, Warren J.; Ramis, Rafael; Weber, Stefan
Abstract: The use of the Laser MegaJoule facility within the shock ignition scheme has been considered. In the first part of the study, one-dimensional hydrodynamic calculations were performed for an inertial confinement fusion capsule in the context of the shock ignition scheme providing the energy gain and an estimation of the increase of the peak power due to the reduction of the photon penetration expected during the high-intensity spike pulse. In the second part, we considered a Laser MegaJoule configuration consisting of 176 laser beams that have been grouped providing two different irradiation schemes. In this configuration the maximum available energy and power are 1.3 MJ and 440 TW. Optimization of the laser–capsule parameters that minimize the irradiation non-uniformity during the first few ns of the foot pulse has been performed. The calculations take into account the specific elliptical laser intensity profile provided at the Laser MegaJoule and the expected beam uncertainties. A significant improvement of the illumination uniformity provided by the polar direct drive technique has been demonstrated. Three-dimensional hydrodynamic calculations have been performed in order to analyse the magnitude of the azimuthal component of the irradiation that is neglected in two-dimensional hydrodynamic simulations.